The Impact of Religion on the Going Concern Reporting Decisions of Local Audit Offices - Omer, Thomas C. (Journal of business ethics, 2018)
We extend research on the effects of local audit office characteristics on audit quality by investigating whether audit offices in highly religious U.S. Metropolitan Statistical Areas (MSAs) exhibit going concern decisions that reflect heightened professional skepticism relative to audit offices in less religious MSAs. Prior research links religiosity to risk aversion and ethical development and suggests audit practice offices in more religious MSAs are more likely to issue going concern opinions because they will assess the effects of mitigating factors in a more skeptical manner. Our results indicate that audit practice offices located in highly religious MSAs are more likely to issue going concern audit opinions, consistent with a more skeptical assessment of mitigating factors. Additional tests provide direct evidence consistent with the argument that these audit offices are more risk averse in issuing going concern opinions. Our findings are relevant to auditors, audit clients, researchers, and regulators.